The FEW-Nexus city index – Measuring urban resilience. (15th January 2018) - Schlör, Holger; Venghaus, Sandra; Hake, Jürgen-Friedrich
Highlights: Development of indices to identify and compare urban FEW nexus. Monitoring, planning and managing the urbanization process in FEW nexus sectors. Operationalization and integration of equity in the FEW nexus analysis. Decision support for urban institutions for the development of political measures. Abstract: Current global developments put increasing ecological, economic and social pressures on urban systems. The density of urban areas concentrates these pressures especially on food, energy and water (i.e., the FEW nexus) resources as if in a 'burning glass'. The ability to confront these challenges significantly depends on the resilience of an urban area, which is to a large degree managed by institutions with the objective of protecting social cohesion and minimizing ecological pressure. Urbanization and climate change, however, strain social cohesion by exacerbating social vulnerabilities and disproportionately affecting those already marginalized. Justice and equity are thus essential preconditions for the development of resilient urban concepts and must be considered in a comprehensive nexus management approach. For this purpose, two indices are developed based on the UN-Habitat City Prosperity Index, with a specific focus on integrating the nexus-relevant indices (i.e., the infrastructure development index and the environmental sustainability index) with a weighted equity index. The World and Region Prosperity City Index (WCPI, RCPI 5 ) and the Nexus City Index (NXI) enable decision makers to more readily compare global and local city resiliences without reducing the underlying complexity of the analyzed FEW system.